2017
DOI: 10.1145/3093336.3037751
|View full text |Cite
|
Sign up to set email alerts
|

Towards Practical Default-On Multi-Core Record/Replay

Abstract: We present Castor, a record/replay system for multi-core applications that provides consistently low and predictable overheads. With Castor, developers can leave record and replay on by default, making it practical to record and reproduce production bugs, or employ fault tolerance to recover from hardware failures. Castor is inspired by several observations: First, an efficient mechanism for logging non-deterministic events is critical for recording demanding workloads with low overhead. Through careful use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
(5 reference statements)
0
26
0
1
Order By: Relevance
“…We categorize this previous work into record-and-replay systems, and deterministic execution systems. Many record and replay (RnR) systems have been proposed both from academia [40][41][42][43][44][45][46] and industry [47][48][49]. These systems record a trace of one nondeterministic execution to enable subsequent replay of that execution, typically for debugging purposes.…”
Section: Related Workmentioning
confidence: 99%
“…We categorize this previous work into record-and-replay systems, and deterministic execution systems. Many record and replay (RnR) systems have been proposed both from academia [40][41][42][43][44][45][46] and industry [47][48][49]. These systems record a trace of one nondeterministic execution to enable subsequent replay of that execution, typically for debugging purposes.…”
Section: Related Workmentioning
confidence: 99%
“…A problem for migrating virtual machine storage also has been designed. Authors in [18][19] proposed the algorithms and found the solution to migrate the virtual machines. There are some other approaches which have been proposed for improving the VM migration.…”
Section: Related Workmentioning
confidence: 99%
“…Carving & Replay와 관련된 몇 가지의 연구들이 이 미 존재한다 [9][10][11][12][13][14]. 이 중 일부는 디버깅을 돕거나 오류 상황을 재현하기 위해 개발되었고 [9][10][11], 일부는 스레드 스케쥴링 같은 동시성의 재현을 위해 개발되었다 [12][13][14]. ADDA [9]…”
Section: 관련 연구unclassified